Analysis of thymidine kinase serum levels by novel method DiviTum in multiple myeloma and monoclonal gammopathy of undetermined significance - comparison with imaging methods 99mTc-MIBI scintigraphy and 18F-FDG PET/CT - Bacovsky, Jaroslav; Myslivecek, Miroslav; Minarik, Jiri; Scudla, Vlastimil; Pika, Tomas; Zapletalova, Jana; Petrova, Pavla; Bartkova, Margita; Adam, Tomas; Gronowitz, Simon J (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
AIMS: The study aimed at comparing two methods for evaluating thymidinekinase TK in serum - an older RIA method and novel DiviTum - in patients with MM and MGUS, and also comparing them with biochemical markers and degree of activity evaluated by imaging methods 99mTc-MIBI scintigraphy and 18F-FDG PET/CT. METHODS: Serum thymidinekinase TK levels were evaluated by DiviTum and an RIA method (TK REA kit by Immunotech);The study analyzed correlation of TK activity in serum with biochemical markers reflecting activity of MM: β2-m, LDH, the ratio of kappa to lambda (κ/λ) free light chains and percentage of bone marrow plasma cells (BMPC). 99mTc-MIBI scintigraphy and 18F-FDG PET/CT were performed at the time of diagnosis. The degree of activity was expressed semiquantitatively. Scans were classified as 0 (normal activity), 1 (diffuse positivity) or 2 (focal positivity). RESULTS: We found a strong positive correlation between TK in serum evaluated by DiviTum and by TK REA.. The DiviTum analytic method extended the detection range and was able to detect higher levels of TK than the RIA method. DiviTum technique found positive correlation with β2-m (r = 0.497) and LDH (r = 0.502) and moderate positive correlation with BMPC (r = 0.368). Significantly higher TK values measured by TK REA and DiviTum in the group of patients with MM (stages I, II or III) than in those with MGUS. Increased TK levels were observed in MIBI- or PET/CT-positive patients. Analysis of repeated measurements of TK in serum during treatment of MM patients found a correlation between change in TK measured by DiviTum and LDH during treatment. CONCLUSIONS: Analysis revealed a significant correlation between TK in serum and LDH, β2-m and BMPC. Increased levels of TK in serum were observed in MIBI- or PET/CT-positive patients. Combination of positivity of imaging methods which can localize active tumor lesions and increased levels of TK in serum can have an impact on decision-making and optimization of the therapeutic approach.
Keywords: dospělí; Female; Monoclonal Gammopathy of Undetermined Significance; Thymidine Kinase; biologické markery; Biomarkers; Adult; ženské pohlaví; Tomography, X-Ray Computed; radiofarmaka; fluorodeoxyglukosa F18; monoklonální gamapatie nejasného významu; lidé; mnohočetný myelom; Radioimmunoassay; Aged, 80 and over; Prohibitins; thymidinkináza; prognóza; Humans; Male; Aged; Prognosis; Radiopharmaceuticals; prohibitiny; lidé středního věku; pozitronová emisní tomografie; senioři nad 80 let; Fluorodeoxyglucose F18; senioři; mužské pohlaví; Multiple Myeloma; radioimunoanalýza; Middle Aged; Positron-Emission Tomography; počítačová rentgenová tomografie